ANALISIS PENDAPATAN USAHA PERTANIAN DAN PETERNAKAN KERBAU DI LOMBOK, NUSA TENGGARA BARAT - S Rusdiana (Departemen Ekonomi Sumberdaya dan Lingkungan, Fakultas Ekonomi dan Manajemen, Institut Pertanian Bogor, 2014)
Agriculture has been a dominant livelihood for the farmers in West Lombok District, West Nusa Tenggara Province. Other than that, farmers usually try to increase their income from livestock. To date, buffalo stock business in rural area has not consider the aspect of benefit at farmers’ level, in contrary to food crops which already shifted to agribusiness. The objective of this research is to analyze farmer’s income at various levels of agriculture and buffalo stock business. The discussion is based on the primary data from field survey and interview with 119 farmers at 4 (four) villages: Umbe, Kuripan, South Kuripan, and Kediri Villages. Secondary data was obtained from the local government agencies and research results. The data was analyzed descriptively and further statistically using two-stage Cochran sampling, t-test, double linear regression, and financial analysis of the food crops and buffalo stock using B/C ratio. The result shows that the average net income from agriculture is IDR 9,90 million/year or equal to IDR 825 thousand/month with B/C ratio 2,7; while net income from buffalo stock is IDR 6,28 million/year or equal to IDR 516 thousand/month with B/C ratio 2,3.